Women's Rights in the Qur'an: A Semiotic Analysis of the Practice of Family Law in Indonesia - Fiqi Halwaini (USRATY : Journal of Islamic Family Law, 2025)
This study examines how women's rights in the Qur'an are symbolically represented and how those meanings are interpreted and practiced within the framework of Islamic family law in Indonesia. Using a semiotic approach, particularly Roland Barthes’ theory of denotation and connotation, this research analyzes how selected Qur'anic verses are understood and operationalized in real-life legal and social contexts. The field research was conducted through in-depth interviews with Islamic family law judges, religious leaders, and female litigants in several religious courts in Indonesia. This approach allows the study to capture the gap between textual meanings and legal practices. The findings indicate that although the Qur'an provides a strong foundation for women's rights in areas such as inheritance, marriage, and social participation, the interpretation and implementation of these rights often vary based on cultural and institutional factors. Semiotic analysis reveals that symbolic meanings embedded in the Qur'anic text are frequently filtered through patriarchal lenses, resulting in interpretations that constrain women's legal agency. This study highlights the importance of recontextualizing Qur'anic messages in line with maqāṣid al-sharī‘ah (the higher objectives of Islamic law), emphasizing justice and equality. The research contributes to the broader discourse on gender and Islamic law by offering empirical insights into how textual meanings interact with lived realities. It calls for a critical yet constructive reinterpretation of the Qur'an that harmonizes ethical intent, legal application, and gender justice in Indonesia’s family law system.